2009
DOI: 10.5551/jat.e265
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Serum Reactive Oxygen Metabolites (ROMs) and Various Inflammatory and Metabolic Parameters in a Japanese Population

Abstract: Aim: Both oxidative stress and inflammation are known to play roles in the pathogenesis of cardiovascular disease. We investigated the relations between reactive oxygen metabolites (ROMs) and various inflammatory and metabolic parameters in a Japanese population. Methods: We analyzed 48 male and 69 female subjects, aged 25 to 65 years, who underwent an annual health checkup in our university. Serum ROM level was assayed using a free radical elective evaluator. We also measured serum concentrations of high-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…Recent studies have shown the usefulness of the evaluation of oxidative stress using d-ROMs. [13][14][15][16] However, this is the first study to measure them simultaneously in a large number of subjects to evaluate oxidative stress from the viewpoint of lifestyle-related disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown the usefulness of the evaluation of oxidative stress using d-ROMs. [13][14][15][16] However, this is the first study to measure them simultaneously in a large number of subjects to evaluate oxidative stress from the viewpoint of lifestyle-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown the positive correlation between the levels of hsCRP and d-ROMs. [14][15][16] Chronic inflammatory processes have been recognized to have a role in the pathogenesis of atherosclerosis. [22][23][24] Therefore, an increase of visceral fat tissue that promotes inflammation, as represented by hsCRP, may have a role in the pathogenesis of atherosclerosis; our result suggests the significance of measuring d-ROMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, selection for high growth potential might have impaired the ability to adapt to oxidative stress and/or accelerated ROS production through higher metabolic rate. Serum d-ROMs are also associated with inflammation (Hirose et al, 2009) and to physical activity (Bloomer and Fisher-Wellman, 2008) in humans. In our study, the differences between the two genotypes are unlikely to result from differences in inflammatory status, as the two breeds did not differ in their acute-phase proteins levels (see below paragraph).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, exercise training decreased the levels of the oxidative stress marker d-ROMs. The usefulness of d-ROMs as an oxidative stress marker has been demonstrated in several studies (28,29), suggesting their association with several diseases (2, 30, 31). In addition, although there was no significant interaction of interventions and time, serum HEL concentrations were significantly decreased in the Ex and S1Ex groups after 12 wk as compared with the baseline values.…”
Section: Discussionmentioning
confidence: 99%